2001
DOI: 10.1161/hh2101.098443
|View full text |Cite
|
Sign up to set email alerts
|

eNOS Activity Is Reduced in Senescent Human Endothelial Cells

Abstract: Abstract-Advanced age is associated with endothelial dysfunction and increased risk for atherosclerosis. However, the mechanisms for these observed effects are not clear. To clarify the association between aging and loss of endothelial function, young human aortic endothelial cells (HAECs), senescent HAECs transfected with control vector, and immortalized HAECs containing human telomerase reverse transcriptase (hTERT) were compared for expression of endothelial nitric oxide synthase (eNOS) and production of NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(170 citation statements)
references
References 41 publications
7
161
2
Order By: Relevance
“…In human iliac arteries, endothelial cells at the bifurcation have shorter telomeres, consistent with a focal acceleration of senescence (3). Senescent human endothelial cells produce less nitric oxide (NO ⅐ ), generate more superoxide anion (O 2 ⅐-), and are more adhesive for monocytes, effects that can be reversed by transfection with the gene encoding telomerase (4).…”
Section: Program In Vascular Medicine and Biology Stanford Universitmentioning
confidence: 99%
“…In human iliac arteries, endothelial cells at the bifurcation have shorter telomeres, consistent with a focal acceleration of senescence (3). Senescent human endothelial cells produce less nitric oxide (NO ⅐ ), generate more superoxide anion (O 2 ⅐-), and are more adhesive for monocytes, effects that can be reversed by transfection with the gene encoding telomerase (4).…”
Section: Program In Vascular Medicine and Biology Stanford Universitmentioning
confidence: 99%
“…This decline in NO availability is a consequence of an impaired eNOS activity as well as of a progressive NO inactivation through increasing levels of superoxide anions. 108,109 As a result, aged vessels exhibit compromised vasodilatory properties that cause increased vascular resistance and impaired perfusion. Moreover, reduced NO bioavailability prompts vascular inflammation and atherogenesis and impedes endothelial repair.…”
Section: Nitric Oxide Signaling In Aging Vessels Is Regulated By Sirt1mentioning
confidence: 99%
“…127,128 Decreases in both NO production and eNOS activity in human umbilical vein endothelial cells and human aortic endothelial cells (HAECs) are associated with aging. 129,130 Matsushita et al 130 demonstrated that shear stress-induced increase in NO production was diminished in senescent HAECs and that stable expression of TERT restored the decreased eNOS expression and NO production associated with aging. Minamino et al 131 reported that HAECs from human atherosclerotic lesions presented phenotypes of senescent cells and decreases in eNOS expression and eNOS activity.…”
Section: Endothelial Cell Senescencementioning
confidence: 99%